Improvement of a tropical residual soil by electrokinetic process - Ahmad, Kamarudin (2004)
Tropical residual soils are generally heterogeneous and partially saturated. These soils attain their strength from capillary stresses as well as cementation of soil particles by clay minerals and sesquioxides. The strength however reduces significantly upon saturation due to the collapse of capillary stresses and increase in pore water pressures. Such strength reductions may lead to soil instability. The effectiveness of additives to increase shear strength however is limited to small soil volume due to slow and restricted ion migration. Thus, electrokinetic (EK) processing was combined with chemical addition to increase ions diffusion. Experiments to study the feasibility of the combined methods to increase the shear strength of a compacted and saturated (C&S) tropical residual soil were performed using EK cells. The diameter and length of each EK cell were 10.0 cm and 5.0 cm, respectively. Open-anode and open-cathode systems were employed to treat soil samples densified to 90% of maximum dry density at the optimum moisture content. Injections of 1.0 M of calcium chloride, aluminium chloride and phosphoric acid were carried out via applications of 30 V DC electrical potential for 168 hours. Effects of EK treatments on compressibility and hydraulic conductivity were also investigated. The employment of distilled water (DW) as anolyte and phosphoric acid (PA) as catholyte resulted in the highest strength and lowest compressibility. The utilisation of the other chemicals as anolytes and DW as catholytes resulted either in strength reduction and higher compressibility or no significant changes in both the engineering properties both near the anodes and the cathodes. EK treatments also affected the values of hydraulic conductivity of the treated soils, depending on the utilised chemicals. On different molarity of PA as catholytes and DW as anolyte, ' the utilisation of 0.5 M PA resulted in the highest cohesion and lowest compressibility of the EK treated soil near the cathode. No significant changes were observed in the compressibility of the treated soils near the anodes from the utilisation of different PA concentrations. Regarding the EK parameters, the directions and quantities of net electroosmotic flows varied depending upon the chemicals used as the anolytes and catholytes. These chemicals influenced the pH of the soil-pore fluid chemistry, which determined the signs and values of zeta potential (<) during EK processing. No net flows were also observed because of isoelectric point (IEP) where < = 0 were achieved. The values of electroosmotic hydraulic conductivity (k,) varied with time and generally lower than the k, values of temperate soils reported in literatures. On different concentrations of PA as catholytes, 0.5 M PA was considered as the optimum concentration in this study because the utilisation of it produced the highest in strength, current density and net electroosmotic flow besides the lowest compressibility. X-ray fluorescence (XRF) analyses on the EK treated samples showed that the distributions of the EK-injected ions after treatments were not uniform.